Regional Predictors and Economic Incorporation of Immigrants: A Multilevel Exploration of Group Size Effects on Occupational Status of Immigrants in Greece - Nikolaos Kolios (European Regional Science Association (ERSA), 2006)
Migration increased tremendously after the 1960s and migrants went to more destinations than before. This fuelled a public discussion over the consequences of migration in the receiving societies. The discussion concerns primarily the economic integration of immigrants and focuses on their high levels of unemployment and low socio-economic status, which are basic aspects of economic incorporation of immigrants. Moreover, local contexts are expected, due to differences in economic structure, labour market characteristics as well as immigrant population size and composition to affect the economic incorporation of immigrants. Immigrant economic incorporation is gradually acknowledged as a problem in Greece. The later belongs to the 'new' immigration countries of the EU and has experienced recent and mass migration. Additionally there is considerable evidence that space features different contexts for the economic incorporation of immigrants in Greece. Literature illustrates different predictors at the level of receiving contexts. Theories regarding the effects of relative immigrant group size on employment argue about different mechanisms. They stress on competing factors such as perceived threat on behalf of the natives and social capital networks that furnish employment for immigrants. Other theories underscore the importance of contextually varying factors such as economic and labour market characteristics namely economic advancement and share of informal activities, rate of unemployment, income inequality and immigrant employment in vulnerable economic sectors or urban labour markets. In this project we use census pooled data and multilevel regression techniques to assess the effects of local contexts on economic incorporation of immigrants in Greece. We test hypotheses regarding the effect of local economic and labour market characteristics as well as immigrant community size on employment and socio-economic status. On the basis of the findings we draw a number of conclusions about economic incorporation of immigrants in Greece.
Keywords: 330